2022
DOI: 10.1111/1756-185x.14293
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of adding pain neuroscience education to a multimodal treatment in fibromyalgia: A systematic review and meta‐analysis

Abstract: The aim of this study was to investigate whether adding pain neuroscience education (PNE) to a multimodal approach has additional benefits in patients with fibromyalgia (FM). The methodology of this study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. The methods and strategies applied in the study were registered in PROSPERO (CRD42021272246). A systematic search with related search terms in the PubMed, Ebsco (Academic Search Ultimate), Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…These findings are consistent with previous reviews, although the level of confidence in our results may be higher due to the higher level of precision in our study ( Sosa-Reina et al, 2017 ). Furthermore, the positive effect of PEBT on pain reduction may be observed in the use of exergames ( Cortés-Pérez et al, 2021 ) or pain neuroeducation programs ( Saracoglu et al, 2022 ) to obtain more improvements. However, our findings did not show statistically significant differences between exercises (such as yoga or tai chi) and other therapies, in contrast to previous reviews ( Cheng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous reviews, although the level of confidence in our results may be higher due to the higher level of precision in our study ( Sosa-Reina et al, 2017 ). Furthermore, the positive effect of PEBT on pain reduction may be observed in the use of exergames ( Cortés-Pérez et al, 2021 ) or pain neuroeducation programs ( Saracoglu et al, 2022 ) to obtain more improvements. However, our findings did not show statistically significant differences between exercises (such as yoga or tai chi) and other therapies, in contrast to previous reviews ( Cheng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, multicomponent therapy, including primarily psychological and exercise therapy, is effective with regard to key fibromyalgia symptoms, self-efficacy, and physical fitness ( Musekamp et al, 2019 ). In a systematic review with meta-analysis, Saracoglu et al (2022) investigated whether the inclusion of pain neuroscience education produces additional benefits in patients with fibromyalgia and showed that pain neuroscience education combined with other non-pharmacological treatments (including exercise therapy) can be effective in improving the condition. Functional, symptoms related to pain, anxiety and depression in these individuals.…”
Section: Introductionmentioning
confidence: 99%
“…
We read with interest the systematic review and meta-analysis (SR/ MA) by Saracoglu et al regarding the efficacy of adding pain neuroscience education (PNE) to a multimodal treatment in fibromyalgia. 1 Fibromyalgia can cause widespread musculoskeletal pain, fatigue, sleep disturbance, cognitive dysfunction, and psychiatric symptoms.Moreover, a lack of consensus on etiopathogenesis, classification criteria, and diagnostic criteria leads to inconsistency of treatment. 2
…”
mentioning
confidence: 99%